PENEGAKAN HUKUM LINGKUNGAN HIDUP DI INDONESIA - ANDY TONGGO MICHAEL SIHOMBING; CHRISTINA NM TOBING (LP2MTBM MAKARIOZ, 2022)
Environment is a gift from God Almighty for all the beings that exist in the world, where none may claim that he is entitled to it from the creatures to the other. Problems of preservation of the environment comes down to sustainability of the environment itself for the survival of all living beings is inversely proportional to the vulgarnya utilization of the environment itself. Can the law and law enforcement in Indonesia to accommodate these problems?. The writing is done by collecting materials by using a normative juridical research method. Normative juridical research is a method of legal research is done by examining library materials and secondary data which is accompanied by an analysis of the provisions of the articles in the legislation as well as the discussions of the expert environmental law from reference books selected. The results of this study lead to the conclusion that Law no. 32 of 2009 concerning the Protection and Management of the Environment as a legal umbrella for environmental administration supported by civil and criminal provisions as hurprecht is sufficiently qualified to create a sustainable living environment. However, on the other hand, there are still inhibiting factors, which require several approaches to enforcing environmental law, the spearhead of which is the need for the firmness of environmental law enforcement officials and the seriousness of the government in carrying out the mandate of the law in question.